Using sequential NETGEN as a component for a parallel mesh generator. (June 2015) - Yilmaz, Y.; Ozturan, C.
Abstract: A parallel tetrahedral mesh generator is developed using the existing sequential NETGEN mesh generator. Mesh generation algorithms developed decompose the geometry into multiple sub-geometries sequentially on a master node and then mesh each sub-geometry in parallel on multiple processors. Two methods are implemented. The first decomposes the geometry and produces conforming surface sub-meshes from which volume meshes can be generated in parallel. A second refinement based method also makes use of the CAD geometry information. A scalable mesh migration algorithm that utilizes "owner updates" rule is implemented. Results show that using the refinement based method, a mesh with a billion elements can be generated in about a minute.